ACHPN Certification Review Course - Stackhouse, Kate; Dials, Cara (Journal of pain and symptom management, 2025)
This instructor-led certification review course is designed to help prepare you for your upcoming Hospice and Palliative Credentialing Center (HPCC) ACHPN certification exam. HPNA Certification Review Courses provide a framework to prepare, and a process to assess strengths and weaknesses of content prior to sitting for an HPCC certification exam. These courses are facilitated by nationally recognized subject matter experts. Each module in the review course addresses sections of the detailed content outline from the 2022 HPCC Candidate Handbook. HPCC is not able to conduct or recommend specific review courses. The use of HPNA exam preparation materials does not imply successful performance on HPCC certification exams. The use of HPNA exam preparation materials does not give an advantage over candidates who do not choose to use them. Continuing Education: Attendees can earn a maximum of 8.75 NCPD hours and 4.0 Category 1 Pharm credits upon successful completion of this course. Successful completion includes attending the activity in its entirety, attesting to attendance, and completing/submitting the postactivity evaluation within the timeframe specified. The faculty/planners of this accredited continuing professional development activity have disclosed no relevant financial, professional, or personal relationship with ineligible companies pertaining to faculty selection, delivery, and evaluation of this conference. The Hospice and Palliative Nurses Association is an accredited provider of nursing continuing professional development by the American Nurses Credentialing Center's Commission on Accreditation (ANCC). Provider number P0284.